Vannamei Shrimp (Litopenaeus vannamei): introduction and description - Adam Setiawan (Academic Letters, 2025)
Vannamei shrimp (Litopenaeus vannamei) is a shrimp native to the Pacific Ocean, precisely west of Mexico, South America and Central America. Currently, vannamei shrimp (Litopenaeus vannamei) is a leading commodity in fisheries cultivation in Indonesia. vannamei shrimp production can be done with high stocking densities and competitive prices, making it a favorite shrimp in Indonesia. This short article discusses vannamei shrimp based on morphological characteristics, habitat, behavior, physiology and life cycle.